A carbon-based iron oxide nanozyme and its preparation method and application

The carbon-based iron oxide nanoenzyme prepared by atomic layer deposition method solves the problems of low catalytic efficiency and lack of target specificity in tumor treatment by tuning the number of ALD cycles, thus achieving high safety and high Carbon-based iron oxide nanoenzyme for tumor treatment effect.

CN116077656BActive Publication Date: 2025-02-11SHANXI MEDICAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310151577.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-02-16
Filing Date
2023-02-22
Publication Date
2025-02-11
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

Existing iron-based nanomaterials have low catalytic efficiency in tumor treatment, low tumor microenvironment response sensitivity, and lack target specificity, which leads to the impact of normal cells and reduces the biosafety of the treatment.

Method used

A cycle-tuned carbon-based iron oxide nanozyme was prepared by atomic layer deposition method. The nanozyme was formed by the deposition of Fe2O3 on the surface of carbon nanospheres and modified by polyethylene glycol for tumor selective ferrode death treatment.

Benefits of technology

The high safety and high tumor treatment effect of nanoenzymes are achieved. By tuning the number of ALD cycles, the selective killing of nanoenzymes on tumor cells and normal cells is accurately controlled, which significantly enhances the tumor treatment effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116077656B_ABST
    Figure CN116077656B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of nanozyme synthesis, and specifically relates to a carbon-based iron oxide nanozyme and its preparation method and application. The present invention utilizes atomic layer deposition of Fe2O3 on the surface of carbon nanospheres and is modified with polyethylene glycol to obtain the carbon-based iron oxide nanozyme. The nanozyme can consume glutathione in the tumor microenvironment and has simulated catalase activity, inducing tumor area redox and ferroptosis of tumor cells. The present invention can precisely control the thickness of the Fe2O3 shell by tuning the number of cycles, and then realize the selective killing of tumor cells and normal cells by the nanozyme controlled by the number of cycles. Under near-infrared laser irradiation, the nanozyme also has excellent photothermal conversion efficiency, which further improves the simulated catalase catalytic activity while photothermally killing tumor cells, thereby significantly enhancing the tumor treatment effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of nanozyme synthesis, and specifically relates to a carbon-based iron oxide nanozyme and a preparation method and application thereof. Background Art

[0002] Ferroptosis is a cell death mechanism that occurs in response to iron and lipid peroxidation processes and shows great potential in the field of cancer therapy, especially in eradicating aggressive malignancies that are resistant to traditional therapies. Emerging iron-based nanomaterials, such as iron oxides, ferrites, and iron-organic frameworks, have been used as ferroptosis inducers to eliminate tumor cells by generating hydroxyl radicals (·OH) via the Fenton reaction with H2O2. On the other hand, the depletion of glutathione (GSH) by iron-based nanozymes leads to the inactivation of GSH-dependent peroxidase 4 (GPX4), which exacerbates the ferroptosis process. However, due to the strict requirements of the Fenton reaction on iron dosage and H2O2 levels, the tumor therapeutic effect of the Fenton reaction is far from satisfactory. More importantly, they lack target specificity, and their "always-on" activity can also cause ferroptosis of normal cells, which has adverse effects on surrounding tissues and human health, further reducing the biosafety of their treatment. Therefore, seeking a nanomaterial that can specifically generate a large amount of ROS in tumor cells and inactivate in healthy tissues is of great significance for safe ferroptosis. Summary of the invention

[0003] Based on the above background, in order to solve the problems of low catalytic efficiency of iron-based nanozymes and low sensitivity of tumor microenvironment response in existing tumor treatments, the present invention uses atomic layer deposition to prepare a new type of nanozyme with tuned cycle number, and applies the nanozyme to tumor selective ferroptosis treatment, which can achieve high safety and high tumor treatment effect of the nanozyme.

[0004] To achieve the above object, the present invention is implemented through the following technical solutions:

[0005] The present invention provides a carbon-based iron oxide nanozyme, which is formed by atomic layer deposition of Fe2O3 on the surface of carbon nanospheres and modification with polyethylene glycol.

[0006] The present invention also provides a method for preparing the carbon-based iron oxide nanozyme, comprising the following steps:

[0007] Step 1, pretreatment of carbon nanospheres: dispersing the carbon nanospheres in water, crushing, and centrifuging to obtain a carbon nanosphere dispersion;

[0008] Step 2, ALD deposition of Fe2O3 on the surface of carbon nanospheres: centrifuge the carbon nanosphere dispersion obtained in step 1 and disperse it in ethanol, apply it on a quartz plate after ultrasonic treatment, air-dry it naturally, and place it in an ALD reactor to cyclically deposit Fe2O3 to obtain C-Fe2O3;

[0009] Step 3, polyethylene glycol modification of C-Fe2O3: Disperse the C-Fe2O3 obtained in step 2 in water, add NH2-PEG2000-COOH, mix and stir to obtain the nanozyme.

[0010] Furthermore, the temperature of the ALD deposition of Fe2O3 in step 2 is 150-300°C.

[0011] Furthermore, the number of cycles of the ALD deposition of Fe2O3 in step 2 is 10-400 cycles.

[0012] Furthermore, in step 2, the metal reaction source for the ALD deposition of Fe2O3 is ferrocene, and the oxygen source is ozone.

[0013] Furthermore, the source temperature of the ferrocene is 70-130°C.

[0014] Furthermore, the pulse time of ferrocene is 5-15s, the holding time is 15-30s, and the nitrogen purging time is 20-60s; the pulse time of ozone is 0.1-0.5s, the holding time is 15-30s, and the nitrogen purging time is 20-60s.

[0015] The present invention also provides the use of the carbon-based iron oxide nanozyme in preparing drugs for tumor treatment.

[0016] Furthermore, the tumor treatment includes photothermal therapy, chemodynamic therapy and ferroptosis therapy. Carbon-based iron oxide nanozymes can consume GSH in the tumor microenvironment and have simulated catalase activity, inducing tumor area redox and tumor cell ferroptosis. Under 808nm near-infrared laser irradiation, carbon-based iron oxide nanozymes also have excellent photothermal conversion efficiency, which further improves the simulated catalase catalytic activity while photothermally killing tumor cells, thereby significantly enhancing the tumor treatment effect. Therefore, the nanozyme of the present invention can be used for photothermal therapy, chemodynamic therapy and ferroptosis therapy of tumors, and has a good synergistic inhibitory effect on tumor growth.

[0017] Furthermore, the tumor is cervical cancer.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The nanozyme of the present invention is prepared by atomic layer deposition technology. Thanks to the controllability, uniformity and conformality of atomic layer deposition technology, the preparation of nanozyme is also precisely controllable.

[0020] (2) The present invention uses confocal microscopy and MTT to demonstrate that carbon-based iron oxide nanozymes can be effectively taken up by tumor cells and stimulate tumor cells to generate a large amount of ·OH, and induce tumor cell death in an iron-dependent manner.

[0021] (2) The biosafety and tumor treatment effect of the nanozyme of the present invention can be tuned by the number of ALD cycles. The thickness of the Fe2O3 shell can be precisely regulated by tuning the number of ALD cycles, and then the selective killing of tumor cells and normal cells by the nanozyme controlled by the number of cycles can be achieved. After 200 cycles of Fe2O3 deposition on the surface of the carbon sphere, the nanozyme has good biocompatibility with cervical epithelial cells, but has a killing effect on HeLa cells; after 25 cycles of Fe2O3 deposition on the surface of the carbon sphere, the nanozyme has a stronger killing effect on cervical epithelial cells than on HeLa cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The microscopic morphology of C-25Fe2O3 and C-200Fe2O3;

[0023] Figure 2 The particle size distribution diagrams of C, C-25Fe2O3@PEG and C-200Fe2O3@PEG;

[0024] Figure 3 Potential diagrams of C, C-25Fe2O3, C-200Fe2O3, C-25Fe2O3@PEG and C-200Fe2O3@PEG;

[0025] Figure 4 The degradation capacity of MB before and after co-incubation of Fe2O3 and GSH with different number of cycles of deposition on the surface of carbon nanospheres;

[0026] Figure 5 Confocal images and corresponding linear scans of HeLa cells cultured with C-200Fe2O3@PEG labeled with rhodamine-B (scale bar: 20 μm);

[0027] Figure 6 Fluorescence image of HeLa cells stained with DCFH-DA;

[0028] Figure 7 The activity data of C-25Fe2O3@PEG and C-200Fe2O3@PEG after acting on HcerEpic cells;

[0029] Figure 8The activity data of C-25Fe2O3@PEG and C-200Fe2O3@PEG after acting on Hela cells;

[0030] Fig. 9 The tumor volumes of tumor-bearing mice during the administration and treatment of normal saline, C-25Fe2O3@PEG, and C-200Fe2O3@PEG;

[0031] Fig.10 The body weight change curves of tumor-bearing mice during the administration and treatment of normal saline, C-25Fe2O3@PEG and C-200Fe2O3@PEG;

[0032] Fig.11 Hematoxylin-eosin staining (HE staining) was used to evaluate the intratumoral necrosis after administration and treatment of normal saline, C-25Fe2O3@PEG, and C-200Fe2O3@PEG;

[0033] Fig.12 TUNEL staining was used to evaluate intratumoral cell necrosis after administration and treatment with normal saline, C-25Fe2O3@PEG, and C-200Fe2O3@PEG. DETAILED DESCRIPTION

[0034] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0035] Example 1: Preparation of Nanozymes

[0036] (1) Pretreatment of carbon nanospheres:

[0037] 100 mg of the purchased carbon nanospheres were dispersed in 40 mL of water to obtain a carbon nanosphere aqueous suspension, the suspension was crushed and dispersed using a cell crusher for 6 h, and then centrifuged at 1000 r / min for 8 min, the supernatant carbon nanosphere dispersion was taken, and the precipitate was discarded;

[0038] (2) ALD deposition of Fe2O3 on the surface of carbon nanospheres

[0039] The carbon nanosphere dispersion was centrifuged and dispersed in ethanol to obtain a 5 mg / mL carbon nanosphere ethanol dispersion, which was coated on a quartz plate after ultrasonic treatment for 20 minutes, naturally air-dried, and placed in an ALD reactor. Ferrocene and ozone were used as precursors and pulses were alternately introduced into the ALD reactor for ALD deposition of Fe2O3. The reaction parameters for ALD deposition of Fe2O3 were as follows:

[0040] The deposition temperature was 200°C; before the ferrocene precursor was introduced into the reactor, it was heated to 100°C to obtain a reasonable vapor pressure; the carrier gas was 50 sccm high-purity nitrogen; for ferrocene, the pulse time was 10 s, the holding time was 20 s, and the nitrogen purge time was 30 s; for ozone, the pulse time was 0.10 s, the holding time was 20 s, and the nitrogen purge time was 30 s;

[0041] The Fe2O3 with deposition cycle numbers of 25 and 200 are denoted as C-25Fe2O3 and C-200Fe2O3, respectively;

[0042] (3) Polyethylene glycol modification of C-Fe2O3

[0043] Disperse C-25Fe2O3 and C-200Fe2O3 in water respectively, take 5mL of 5mg / mL C-25Fe2O3 or C-200Fe2O3 aqueous solution, and add 25mg NH2-PEG 2000 -COOH, mix and stir for 24 hours, and wash with deionized water three times to obtain nanozymes C-25Fe2O3@PEG and C-200Fe2O3@PEG.

[0044] Characterization test: such as Figure 1 As shown in the figure, the Fe2O3 on the surface of C-25Fe2O3 is small particles, and the Fe2O3 on the surface of C-200Fe2O3 is a film layer of a certain thickness. Figure 2 As shown in Figure 2, the particle sizes of C, C-25Fe2O3@PEG and C-200Fe2O3@PEG are 159.43±2.55nm, 166.33±1.31nm and 170.47±6.91nm, respectively. Figure 3 As shown, the potentials of C, C-25Fe2O3, C-200Fe2O3, C-25Fe2O3@PEG and C-200Fe2O3@PEG are: -23.50±1.45mV, -22.60±1.83mV, -19.43±3.19mV, -8.84+-0.71mV and -5.7+-1.129mV, respectively.

[0045] Example 2: GSH-responsive Fenton reaction of nanozymes

[0046] The degradation of methylene blue (MB) was used to analyze the Fenton reaction of nanozymes before and after GSH incubation after different cycles of Fe2O3 deposition on carbon nanospheres. The Fe2O3 cycles of 0, 10, 25, 50, 100, 200, and 400 were selected to prepare C, C-10Fe2O3, C-25Fe2O3, C-50Fe2O3, C-100Fe2O3, C-200Fe2O3, and C-400Fe2O3 nanozymes. A certain concentration of nanozymes and GSH were added to NaHCO3 / CO2 buffer solution and incubated at 37°C for 2h. Then, the incubated mixture was added to MB solution containing H2O2 and incubated at 37°C for 60min, and the absorbance of MB at 665nm was recorded. In order to study the effect of GSH on the chemokinetic activity, the above experiment was repeated using the same concentration of nanozymes without GSH incubation.

[0047] Figure 4 The degradation ability of MB before and after co-incubation of Fe2O3 and GSH with different number of cycles of deposition on the surface of carbon nanospheres is shown. It can be seen that among the nanozymes not incubated with GSH, C-25Fe2O3 has the strongest degradation ability for MB, indicating that small-particle Fe2O3 has a higher Fenton activity and C-25Fe2O3 has the strongest degradation ability for MB; while C-200Fe2O3 without GSH co-incubation has a very weak degradation ability for MB, indicating that the film-forming Fe2O3 has a very weak Fenton activity. After the nanozyme was co-incubated with GSH, its degradation ability for MB changed. The Fe2O3 of both nanozymes was partially reduced to Fe by GSH. 2+ However, due to the small iron loading of C-25Fe2O3, the Fenton activity decreased after GSH incubation; C-200Fe2O3 had a large iron loading, and its Fenton activity increased after GSH incubation.

[0048] Example 3: HeLa cell uptake of nanozymes

[0049] To prove that nanozymes can be taken up by HeLa cells, the uptake of nanozymes labeled with rhodamine B fluorescence by tumor cells was investigated. After HeLa cells were inoculated in the confocal dish for 24 hours, the culture medium was aspirated, and nanoparticles were added at a pre-set concentration. After 2 hours, 4 hours, and 6 hours of cell uptake, the nanoparticles were aspirated, washed with phosphate buffered saline (PBS), fixed with 4% paraformaldehyde for 20 minutes, and stained with nuclear dye (DAPI reagent) in the dark for 30 minutes, the qualitative results of cell uptake were investigated under a laser confocal microscope.

[0050] Figure 5 These are the qualitative results of the uptake of C-25Fe2O3@PEG and C-200Fe2O3@PEG by HeLa cells. It can be seen that the fluorescence intensity in the HeLa cells reaches a plateau at 6 hours, indicating that the uptake of the nanozymes by HeLa cells reaches saturation at this time.

[0051] Example 4: Cell-selective killing tuned by nanozyme cycle number

[0052] To prove that the number of atomic layer deposition cycles can tune the biosafety and ferroptosis of cervical epithelial cells and HeLa cells, dichlorofluorescein diacetate probe (DCFH-DA) was used to measure the reactive oxygen species in cervical epithelial cells and tumor cells after treatment with two nanozymes, C-25Fe2O3@PEG and C-200Fe2O3@PEG; cervical epithelial cells and HeLa cells were inoculated in culture dishes and cultured for 24 hours, and the cell culture incubator containing C-25Fe2O3@PEG or C-200Fe2O3@PEG was incubated for 4 hours, and the prepared DCFH-DA probe dilution was added and incubated for another 0.5 hour, then the cells were taken out, washed twice with PBS, and the nuclei were fixed and stained, and the changes in intracellular ROS levels were observed by laser confocal microscopy.

[0053] In addition, the biocompatibility and tumor cell toxicity of the nanozyme were investigated by MTT assay. After 24 h of incubation with the drug for cervical epithelial cells and HeLa cells, the procedure was performed according to the instructions of the kit, and the ultraviolet absorption was measured by a microplate reader to calculate the cell survival rate.

[0054] like Figure 6 As shown in the figure, HeLa cells treated with C-200Fe2O3@PEG have strong UV absorption, while HeLa cells treated with C-25Fe2O3@PEG have weak UV absorption, indicating that C-200Fe2O3@PEG can indeed drive the Fenton reaction to produce a large amount of ·OH; in contrast, the Fenton activity of C-25Fe2O3@PEG in the tumor microenvironment is very weak. Figure 7 and Figure 8 As shown in the figure, the survival rate of cervical epithelial cells treated with C-200Fe2O3@PEG was higher than that of C-25Fe2O3@PEG, and the survival rate of HeLa cells treated with C-25Fe2O3@PEG was higher than that of C-200Fe2O3@PEG. C-200Fe2O3@PEG has better biocompatibility and stronger ability to promote tumor ferroptosis than C-25Fe2O3@PEG. At the same time, after treating HeLa cells with C-200Fe2O3@PEG or C-25Fe2O3@PEG with 808nm laser irradiation, the survival rate of HeLa cells was further reduced, and photothermal and chemical kinetics can synergistically kill tumor cells.

[0055] Example 5: Pharmacodynamic evaluation of nanozymes in animal models of cervical cancer

[0056] Tumor-bearing mice were randomly divided into 6 groups, with 5 mice in each group, namely (1) PBS group; (2) PBS+808nm laser group; (3) C-25Fe2O3@PEG group; (4) C-200Fe2O3@PEG group; (5) C-25Fe2O3@PEG+808nm laser group; (6) C-200Fe2O3@PEG+808nm laser group. 2 mg / kg nanodrug or the same volume of saline was injected into the tail vein for 2 times. The changes in mouse body weight and tumor size were recorded. After the drug administration cycle, the mice were killed and the tumor volume was recorded. The tumor tissues were taken for HE staining and TUNEL staining.

[0057] Fig. 9 The tumor volumes of tumor-bearing mice in each group during the administration period are shown. Regardless of laser irradiation or not, the tumor growth of tumor-bearing mice after administration of C-200Fe2O3@PEG was more significantly inhibited compared with the C-25Fe2O3@PEG group, indicating that C-200Fe2O3@PEG is more conducive to triggering ferroptosis than C-25Fe2O3@PEG; Fig.10 The results of the body weight curves showed that the two nanozymes did not cause weight loss in mice during the treatment period, indicating that the nanozymes had no systemic toxicity; Fig.11 The results of HE staining of tumor tissue showed that the necrosis area of ​​the tumor in the C-200Fe2O3@PEG group was larger than that in the C-25Fe2O3@PEG group, indicating that C-200Fe2O3@PEG had a better tumor inhibition effect. Fig.12 In TUNEL staining, the C-200Fe2O3@PEG-treated group had a larger fluorescence area, which was consistent with the HE staining results.

[0058] The above results indicate that the nanozymes prepared by atomic layer deposition constructed in the present invention can achieve selective killing of normal cells and tumor cells by adjusting the cycle number, and the nanozymes prepared by rationally designed and selected cycle numbers have the best tumor inhibition effect and biosafety.

[0059] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0060] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. Application of a carbon-based iron oxide nanozyme in the preparation of a drug for the treatment of cervical cancer, characterized in that: The nanozyme is formed by atomic layer deposition of Fe2O3 on the surface of carbon nanospheres and modified with polyethylene glycol; the cervical cancer treatment includes photothermal therapy, chemodynamic therapy and ferroptosis therapy.

2. The use of the carbon-based iron oxide nanozyme according to claim 1, characterized in that: The preparation method of the nanozyme comprises the following steps: Step 1, pretreatment of carbon nanospheres: dispersing the carbon nanospheres in water, crushing, and centrifuging to obtain a carbon nanosphere dispersion; Step 2, ALD deposition of Fe2O3 on the surface of carbon nanospheres: centrifuge the carbon nanosphere dispersion obtained in step 1 and disperse it in ethanol, apply it on a quartz plate after ultrasonic treatment, air-dry it naturally, and place it in an ALD reactor to cyclically deposit Fe2O3 to obtain C-Fe2O3; Step 3, polyethylene glycol modification of C-Fe2O3: Disperse the C-Fe2O3 obtained in step 2 in water, add NH2-PEG2000-COOH, mix and stir to obtain the nanozyme.

3. The use of the carbon-based iron oxide nanozyme according to claim 2, characterized in that: The temperature of the ALD deposition of Fe2O3 in step 2 is 150-300°C.

4. The use of the carbon-based iron oxide nanozyme according to claim 2, characterized in that: The number of cycles of ALD deposition of Fe2O3 in step 2 is 10-400.

5. The use of the carbon-based iron oxide nanozyme according to claim 2, characterized in that: The metal reaction source for the ALD deposition of Fe2O3 in step 2 is ferrocene, and the oxygen source is ozone.

6. The use of the carbon-based iron oxide nanozyme according to claim 5, characterized in that: The source temperature of the ferrocene is 70-130°C.

7. The use of the carbon-based iron oxide nanozyme according to claim 5, characterized in that: The pulse time of ferrocene is 5-15s, the holding time is 15-30s, and the nitrogen purging time is 20-60s; the pulse time of ozone is 0.1-0.5s, the holding time is 15-30s, and the nitrogen purging time is 20-60s.

Citation Information

Patent Citations

  • Preparation method of bimetallic nano-enzyme composite material with anti-tumor effect

    CN113398285A